Family and peer influences on adolescent psychological inflexibility: a regression mixture analysis - Liu, Lei; Hu, Xiaomeng; Ma, Mengyu; Zhang, Weilu; Peng, Biao; Zhang, Bixia; Luo, Xiaofang (Frontiers in Psychology, 2025)
IntroductionAdolescent mental health problems are closely linked to psychological inflexibility. Prior research has identified separate effects of family functioning and peer relationships on psychological inflexibility, but their combined effects (particularly from a person-centered perspective) remain underexplored. We use a person-centered regression mixture approach to jointly model family functioning and peer relationships and examine their joint associations with adolescent psychological inflexibility.MethodsThe study surveyed 940 adolescents using the Family APGAR Index, the Peer Relationship Scale, and the Avoidance and Fusion Questionnaire for Youth to measure family functioning, peer relationships, and psychological inflexibility, respectively.ResultsThrough latent class analysis (LCA), six latent classes representing combined patterns of family functioning and peer relationships were identified. Adolescents exposed to both low family functioning and low peer relationships showed the highest psychological inflexibility, whereas those with high family functioning and high peer relationships showed the lowest. Regression mixture results indicated significant differences in psychological inflexibility across classes.ConclusionThese findings highlight the joint influence of family functioning and peer relationships on adolescent psychological inflexibility and suggest that interventions should concurrently target both environments to reduce inflexibility and improve mental health outcomes.